Attribution to success and failure for Thai athletes in the 1st Asian indoor games - Srijunwong, S. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: There are a number of ways in which to maintain a high level of motivation by athletes in order to achieve their goals. Attribution theory has been used to explain athletes` behaviour through reasons they give after success or failure in sports. The first objective of this study was to identify such reasons of Thai national athletes` who participated in the first Asian Indoor Games in 2005. A comparison between genders, ages, groups and sports performance perceptions (success or failure) of the participation athletes toward their games was also conducted. Methods A validated questionnaire which consisted of 45 items (under 4 areas) to identify athletes` reasons toward their success and failure (Sarutee Srijunwong, 1993) was administered to 103 athletes. The athletes ranged in age from 14-36 years (Mean = 17.78, SD = 9.02) from 9 different team and individual indoor sports. Results The effectiveness of the size values were calculated among genders, age groups and perceived of success and failure for this study. Statistical analysis revealed that: (1) Male/female athletes of any age group gave similar reasons for their sport success and failure. In particular, luck was found to be the first reason they gave after the games, while permanent effort was the last in all categories tested. (2) The effect size which was analysed on gender and age groups indicated that: Males and females had similar reason for their success and failure (ES = 0.14 - 0.01). Athletes in the under 18 years old group were moderately different from the older aged groups (ES = -0.53 to 0.02) The perceived athlete success group were significantly different compared to the perceived failure athlete group (ES= 2.74- 0.25). Discussion / Conclusions The order of reasons given for success and failure of the athletes varied between groups. The comparison was indicated to various levels of difference. Perceptions of the success and failure between groups were clearly different. for a broad range of reasons.